Knowledge, attitude, intention, and program implementation of iron supplementation among adolescent girls in Sidoarjo, Indonesia - Hanna T. Hasianna Silitonga; Lutfi A. Salim; Ira Nurmala; Rachmat Hargono; Septiana Purwandini (Journal of Public Health in Africa, 2023)
Background: The government established an iron supplementation program as a solution to overcome anemia in adolescent girls in Indonesia. Research shows that various factors influence the compliance of adolescent girls in consuming iron supplements, including knowledge, attitude, intention, and program implementation.